Identifikasi Kecurangan Dan Whistleblowing Universitas - Hapsari, Aprina Nugrahesthy Sulistya; Seta, Dally Wahyu (Jurnal Riset Akuntansi dan Keuangan, 2019)
Abstract. This research aims to identify the potential for fraud at the university and determine the extent of individual intentions in the financial and accounting units and the assets section to reveal the occurrence of fraud discovered. Universities are institutions that should have good internal control mechanisms and university governance and are supported by an assessment of university quality assurance, so as to prevent fraud. The mechanism proposed in this research is a whistleblowing system which is triggered by the willingness of accounting financial managers and assets of a university to be brave and willing to disclose fraud. The intention of whistleblowing was traced by case studies at a private university in Central Java. The results of this research indicate that the potential for fraud that occurs in tertiary institutions is in terms of the procurement of goods and services, as well as the operational realization of the budget. Other findings indicate that whistleblowing intentions are supported by a positive attitude of oneself, subjective norms that come from the support of the people around and the norms that apply, and ease in reporting fraud. Feeling reluctant is an obstacle to the existence of a whistleblowing, but a sense of loyalty and having a high level of respect for the university makes the intention and desire to report fraud remains the main choice.Â Abstrak. Riset ini bertujuan mengidentifikasi potensi kecurangan di universitas dan mengetahui sejauhmana niat individu pada unit bagian keuangan dan akuntansi serta bagian asset untuk mengungkapkan terjadinya kecurangan yang ditemukan. Universitas merupakan lembaga yang seharusnya memiliki mekanisme pengendalian internal dan tata kelola universitas yang baik serta didukung dengan adanya penilaian atas penjaminan mutu universitas, sehingga mampu mencegah terjadinya kecurangan. Mekanisme yang diusulkan dalam riset ini adalah whistleblowing system yang dipicu oleh kemauan para pengelola keuangan akuntansi dan aset suatu universitas untuk berani dan mau mengungkapkan kecurangan yang terjadi. Niat whistleblowing ditelusuri dengan studi kasus pada satu universitas swasta di Jawa Tengah. Hasil riset ini menunjukkan bahwa potensi kecurangan yang terjadi pada perguruan tinggi adalah dalam hal pengadaan barang dan jasa, serta operasional realisasi anggaran. Temuan lain menunjukkan bahwa niat whistleblowing didukung oleh sikap positif dari diri sendiri, norma subjektif yang berasal dari dukungan orang disekitar serta norma yang berlaku, dan kemudahan dalam melaporkan adanya tindak kecurangan. Rasa sungkan menjadi kendala adanya whistleblowing, namun rasa loyal dan memiliki yang tinggi terhadap universitas membuat niat dan keinginan untuk melaporkan kecurangan tetap menjadi pilihan utama.Kata Kunci: Kecurangan; Universitas; Whistleblowing.